Framing Media Terhadap Ulama Di Balik Popularitas Jokowi dan Prabowo - Ardianti, Raissa (Jurnal Transformative, 2018)
The easy access to online media made the electoral progress of Jokowi and Prabowo in-teresting to be watched. There are many perspectives and facts regarding both candi-dates that elevate the publicâs argumentation in the public sphere. However, the easy ac-cess of that online media un-fortunately had created a bias between both candidatesâ true modality and the issues behind them. The Islamic value of the Ulama behind both candi-dates are the most interesting issues of them all. Indonesian society began to pay more attention to Ulamaâ figure instead of to the modalities both candidates promoted. This writing aims to drive that public partiality about the Ulama trough paying more attention to the electability level by affirming Talal Asadâs thesis about Ulama and Politics.